Sex and Labor Trafficking in Paraguay: Risk Factors, Needs Assessment, and the Role of the Health Care System - Stanford, Kimberly (Journal of interpersonal violence, 2021)
Trafficking of adults and children for both sex and labor is a human rights violation occurring with alarming frequency throughout the world, and resulting in profound harm to close-knit communities and severe health consequences for victims. Certain areas, such as the country of Paraguay, are at a higher risk for trafficking due to unique economic, cultural, and geographic factors. Thousands of people, especially children, are trafficked within Paraguay’s borders, and many eventually are transported to neighboring countries and sometimes to Europe and elsewhere. Using case study methodology and “city” as the unit of study, researchers interviewed 18 key anti-trafficking stakeholders from government and nongovernmental organizations in two major metropolitan centers for trafficking in Paraguay, Asunción, and Encarnación. Through semistructured interviews, this qualitative study examines risk factors for trafficking, health outcomes, interventions needed within the health care sector, and programs needed to combat trafficking. We identified risk factors including poverty, marginalization of indigenous people, gender inequality, domestic servitude of children (criadazgo), and political hesitance to enact protective legislation. Victims of trafficking were reported to suffer from physical injuries, unintended pregnancies, sexually transmitted infections, and mental health issues such as depression and posttraumatic stress disorder. These predispose victims to difficulties reintegrating into their communities and ultimately to retrafficking. A major gap was identified in the lack of sufficient lodging and rehabilitation services for rescued victims, affordable access to trauma-sensitive health care for victims, and scarce mental health services. Many of the findings are applicable across the world and may be of use to guide future anti-trafficking efforts in Paraguay and beyond.